Refleksje o godności człowieka w starzejącym się społeczeństwie - Kuchciak, Anna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
Given the ageing of society, issues involving the elderly are becoming increasingly discussed publicly by representatives of various environments. While demographic changes entail multi-faceted consequences, attention is mainly being focused on the tangible effects of the increasing number of elderly people. The article contains reflections on the slightly less measurable but relevant issue of respect for the human dignity in an ageing society and highlights the appropriate constitutional as well as statutory regulations
Keywords: godność człowieka; osoby starsze; społeczeństwo